2019
DOI: 10.1128/jvi.01749-18
|View full text |Cite
|
Sign up to set email alerts
|

Histidine-Rich Glycoprotein Inhibits HIV-1 Infection in a pH-Dependent Manner

Abstract: Histidine-rich glycoprotein (HRG) is an abundant plasma protein with a multidomain structure, allowing its interaction with many ligands, including phospholipids, plasminogen, fibrinogen, IgG antibodies, and heparan sulfate. HRG has been shown to regulate different biological responses, such as angiogenesis, coagulation, and fibrinolysis. Here, we found that HRG almost completely abrogated the infection of Ghost cells, Jurkat cells, CD4+ T cells, and macrophages by HIV-1 at a low pH (range, 6.5 to 5.5) but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…Then, Vero cells were cultured for three days in a sulphate-free medium supplemented with sodium chlorate, an inhibitor of sulphation. As we previously shown [ 40 ], this treatment resulted in a marked reduction (> 90%) in the expression cell surface HS (data not shown). These cells were incubated with ZIKV at pH 7.3 or 6.2 for 1 h, washed, and incubated for 48 h at 37°C.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Then, Vero cells were cultured for three days in a sulphate-free medium supplemented with sodium chlorate, an inhibitor of sulphation. As we previously shown [ 40 ], this treatment resulted in a marked reduction (> 90%) in the expression cell surface HS (data not shown). These cells were incubated with ZIKV at pH 7.3 or 6.2 for 1 h, washed, and incubated for 48 h at 37°C.…”
Section: Resultssupporting
confidence: 83%
“…In fact, low pH values (range 6.0 to 7.0) have shown to increase the binding of a variety of proteins, such as the prion protein, gp64 of baculovirus, GM-CSF, selenoprotein P, vascular endothelial growth factor, and the nonfibrillar form of beta-amyloid peptide to HS via protonation of histidine residues [53][54][55][56][57][58] The ability of low pH to increase the binding of viruses to target cells is not exclusive of ZIKV. We have previously reported that low pH enhances the binding of HIV-1 to spermatozoa and epithelial cells, but not to CD4+ T cells or dendritic cells 40,44 .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…It is important to note that Cst-3 is not the only HS-binding protein that displayed acidic pH-dependence. In fact, histidine-rich glycoprotein protein, which contains two cystatin-like domains, has been shown to bind HS in an acidic pH-dependent manner 21 , 22 . Other examples include selenoprotein P 23 , serum amyloid A 24 , diphtheria toxin 25 , and gp64 26 .…”
Section: Discussionmentioning
confidence: 99%